PENGENDALIAN KUALITAS PRODUK WOOD PELLET MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL (SQC) DI PT. YALE WOODPELLET INDONESIA - Rohmat, Rohmat; Wahyu Darmawan, Dimaz; Adilla Tristianto, Charismanda (JUSTI (Jurnal Sistem dan Teknik Industri), 2026)
The increasing demand for renewable energy has encouraged the wood pellet industry to produce products that meet international quality standards. PT. Yale Woodpellet Indonesia, as a wood pellet manufacturer, needs to implement an effective quality control system to maintain consistent product quality. This industrial internship aims to analyze the quality level of wood pellet products, identify dominant types of defects, evaluate the stability of the production process, and propose improvement strategies using the Statistical Quality Control (SQC) method. The data used consist of primary data obtained through direct observation during the production period and secondary data from company documents. The SQC tools applied include check sheets, data stratification, histograms, scatter diagrams, P control charts, Pareto diagrams, and cause-and-effect diagrams. The analysis results show that out of a total production of 7949 wood pellet units, 271 defective units were identified, resulting in a defect rate of 3.4%. The P control chart indicates that the production process is statistically under control after the elimination of extreme data. Pareto diagrams and histograms identify excessive moisture content as the dominant type of defect. The main causes of defects are variations in raw material quality, machine conditions, work methods, and human factors. Based on these findings, improvements are recommended in the form of enhanced control of the drying process, standardization of operating procedures, operator training, and regular machine maintenance to improve the quality of wood pellet products.